The National Coloring as a Part of the Connotative Meaning of Realia - Yerbulatova, Ilmira; Gilazetdinova, Gelinya; Aminova, Almira; Utegenova, Karlyga (Journal of History Culture and Art Research, 2018)
The article deals with the definition of the concept of coloring, as well as the significance of its role in cultural-oriented units - the realities and ways of their translation. The study was conducted on the basis of the small genres of Kazakh fiction at the end of the 20th and beginning of the 21st centuries, short stories by Dukenbai Doszhan "Kelinshek Asuy", "Shortanbai", "Kukpar" and their translations into Russian, performed by the native speakers of the translation language "The Pass of a Young Woman" translated by I. Ukhanov, "Shortanbay" and "Kokpar" translated by Z. Nikolaeva. The main research methods were the analytical method and comparative analysis of translations with original prose from Kazakh into Russian. As a result of the research, various definitions of the concept of color were analyzed with the purpose of identifying elements characteristic of the term “realia” (“reality”), and a special role of color in revealing connotative features of realities and, accordingly, methods of transforming such units in the process of artistic translation. The main results of the research presented in the article provide an opportunity to find out how the typical tasks of the artistic translation of the Kazakh realities are implemented to recreate the specific national and cultural background of the Kazakh language picture of the world.